Podróż Mikołaja Sienickiego po terytorium Korony w pierwszych miesiącach bezkrólewia po śmierci Zygmunta Augusta (lipiec-październik 1572 r.) - Adamkiewicz, Sebastian (Acta Universitatis Lodziensis. Folia Historica, 2010)
On December 13th 1572 the convention of Ruthenian nobility gathered in Sadowa Wisznia before the convocation. The consequent confederation act contained extremely detailed legislative proposals, designed to solve problems of Polish-Lithuanian Commonwealth, which had appeared after childless death of king Zygmunt August. So far literature have suggested that the aforementioned act was a result of extraordinary political maturity of Ruthenian nobility. But most of the historians did not note that Mikolaj Sienicki, famous leader of so called enforcement movement, took part in Wisznia’s convention. Before that event he had made a long journey across the Kingdom of Poland (July-October 1572). It gave him an opportunity to be a witness of uncompromising political war, which started in the first days of interregnum. He took part in 6 nobility conventions, 3 of which had higher status than just local. His observations enabled Ruthenian nobility to made analysis of real situation in Commonwealth.